(untitled) (Research, Society and Development, 2021)
Theoretical framework: cancer is a group of more than one hundred diseases, of which have intrinsic and/or extrinsic factors, modifiable and non-modifiable for its onset. Vitamin D, in turn, is a steroid hormone that has its biological actions mediated by the vitamin D receptor, consequently developing roles related to the control of cell growth, differentiation and proliferation, in which, the administration of its active metabolites or analogues can result in inhibition of angiogenesis, delegating effects antiproliferative and activation of apoptotic mechanisms. Objective: Present the influence of vitamin D action on cancers that affect the gastrointestinal tract and distinct organs. Methodology: It is an integrative review, with a qualitative approach. Based on research on BVS and PubMed databases, 19 articles were selected that were consistent with the theme and the inclusion and exclusion criteria, through the association of descriptors and keywords. Results: 84.62% and 71.43% of the studies demonstrated a positive correlation of vitamin D in the anti-carcinogenesis process of cancers that affect the gastrointestinal tract and different organs, respectively. The carcinogenesis process can be influenced by vitamin D deficiency, polymorphisms in the vitamin D receptor gene and other changes and relationships with underlying pathways. Conclusion: This study highlights the positive influence of vitamin D in the prevention of carcinogenesis that affects the gastrointestinal tract and different organs.